Robust Sensor Fault Detection and Estimation for Parabolic Distributed Parameter Systems - Wang, Kui; Zhou, Jinhui; Shen, Wenjing; Zhou, Yu; Wei, Peng; Mou, Xiaolin; Chen, Liqun (IEEE transactions on instrumentation and measurement, 2025)
Sensors play a key role in monitoring distributed parameter systems (DPSs), such as thermal and chemical diffusion-reaction processes. However, sensor faults can result in data distortion, degraded system performance, and even catastrophic consequences. This article proposes a model-based sensor fault diagnosis framework for DPSs, which can effectively detect the fault time and estimate the fault intensity. The proposed method only requires the limited measured output without any state information. Besides, noise will cause perturbations in the sampling data. Correspondingly, a linear matrix inequality (LMI) considering disturbance is designed. Through theoretical analysis, the convergence of fault estimation error is ensured. The effectiveness of the proposed method is verified on a heat transfer rod and a chemical diffusion-reaction system with static and time-varying sensor faults under disturbances. The root mean square errors of all sensor fault estimates are within 0.1078.